Analysis of genomic sequences from peanut (Arachis hypogaea) - Jayashree, B.; Ferguson, Morag E.; Illut, D.; Doyle, J.; Jonathan, H. (Electronic Journal of Biotechnology, 2005)
Peanut is an important legume crop across the world. However, in contrast to most legume crops, groundnut lacks taxonomic proximity to any major model genome. A relatively large number of genomic sequences were generated from groundnut as part of a microsatellite marker development project. In the current study, a total of 1312 sequences were analyzed of which 448 contained microsatellite motifs. All sequences (GenBank Accessions: BZ999351-CC000573) were analyzed after clustering for possible similarity with publicly available sequences from Arabidopsis, Lotus, soybean and Medicago. At least 39% of the sequences analyzed had significant BLAST similarities with sequences from the four databases searched, of which nearly half (47%) found significant similarity with Lotus japonicus sequences. Over one quarter (26.7%) of sequences found similarity with Arabidopsis thaliana, while the remainder aligned with publicly available sequences from the legumes soybean and Medicago truncatula. At least 17% of microsatellite containing sequences could be assigned an identity. The codon usage pattern for Arachis hypogaea most closely resembles that of L. japonicus reflecting the similarly high sequence similarity observed in BLAST searches at the protein level. The implications of these findings for the taxonomy, and comparative genomics of groundnut and its legume family relatives are discussed.